2009
DOI: 10.1021/ma802579g
|View full text |Cite
|
Sign up to set email alerts
|

Chemo-Enzymatic Synthesis of Poly(lactate-co-(3-hydroxybutyrate)) by a Lactate-Polymerizing Enzyme

Abstract: In our previous paper, we synthesized poly-3-hydroxybutyrate [P(3HB)] by using the waterorganic-solvent two-phase reaction system (TPRS), in which (R)-3-hydroxybutyrylCoA [(R)-3HBCoA] was continuously supplied to PHA synthase by the ester exchange reaction between CoA and thiophenol in thiophenyl (R)-3HB [(R)-3HBTP]. By applying TPRS to the screening, we found a lactate-(LA-) polymerizing enzyme from PHA synthases. The enzyme was an engineered PHA synthase, which stereoselectively copolymerized (R)-LA together… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 38 publications
2
27
0
1
Order By: Relevance
“…PhaC1STQK was originally created through the engineering of PHA synthase in order to enhance the activity toward 3HB-CoA (Taguchi and Doi, 2004;Takase et al, 2003). The activity of PhaC1STQK toward LA-CoA was found by means of an in vitro chemo-enzymatic synthesizing system and formally designated LPE (Taguchi et al, 2008;Tajima et al, 2009). The result of the present study demonstrated that PhaC1STQK also recognized glycolyl-CoA as a monomer substrate.…”
Section: Discussionmentioning
confidence: 71%
“…PhaC1STQK was originally created through the engineering of PHA synthase in order to enhance the activity toward 3HB-CoA (Taguchi and Doi, 2004;Takase et al, 2003). The activity of PhaC1STQK toward LA-CoA was found by means of an in vitro chemo-enzymatic synthesizing system and formally designated LPE (Taguchi et al, 2008;Tajima et al, 2009). The result of the present study demonstrated that PhaC1STQK also recognized glycolyl-CoA as a monomer substrate.…”
Section: Discussionmentioning
confidence: 71%
“…Thus, replacement of the heavy metal catalyst with a safe and environmentally acceptable alternative is an important issue. To this end, one-pot production of PLA and its copolymers was achieved using the newly established microbial cell factory integrated by a lactatepolymerizing enzyme (LPE) (refer to section 1.2.3) [36,37].…”
Section: Plasmentioning
confidence: 99%
“…The first indication of LA-polymerizing activity was obtained through a water-organic solvent two-phase in vitro system [36,37]. The activity towards LA-CoA was tested in the absence and presence of 3HB-CoA using representative PHA synthases belonging to the four classes of natural PHA synthases, together with three engineered (PhaC1 Ps mutants) from Pseudomonas sp.…”
Section: Creation Of Lactate-polymerizing Enzyme (Lpe)mentioning
confidence: 99%
“…The advantages and disadvantages of the PLA synthesis methods mentioned above are summarized in Table 2. In the bio-process, the LA monomer is converted into LA-CoA ,which is recognized by the LA-polymerizing enzyme recruited from microbial PHA synthase (Tajima et al, 2009 …”
Section: New Approachesmentioning
confidence: 99%